2021
DOI: 10.3897/vz.71.e69214
|View full text |Cite
|
Sign up to set email alerts
|

Comparative ecomorphology of the sandstone night lizard (Xantusia gracilis) and the granite night lizard (Xantusia henshawi)

Abstract: It is hypothesized that shape differences between the closely related sandstone night lizard (Xantusia gracilis) and the granite night lizard (X. henshawi) may be correlated with structual differences in their respective microhabitats. Multivariate and univariate analyses of 22 morphometric characters taken from the head, body, and limbs of both saxicolus specialists recovered statistically significant differences between them with X. gracilis having a wider head, longer snout, larger eyes, wider sternum, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, some of the rock dwelling species differ significantly from one another as well (Tables 4, 5). This would indicate that, although these species occupy rocky habitats, they may be doing so differently as has been seen in other closely rock-dwelling species (e.g., Grismer 2021). Within other studies, a correlation between habitat type and (Herrel et al 2001).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, some of the rock dwelling species differ significantly from one another as well (Tables 4, 5). This would indicate that, although these species occupy rocky habitats, they may be doing so differently as has been seen in other closely rock-dwelling species (e.g., Grismer 2021). Within other studies, a correlation between habitat type and (Herrel et al 2001).…”
Section: Discussionmentioning
confidence: 91%
“…Ecomorphological studies of morphological adaptations in lizards have revealed that head, body, and limb proportions bear significantly on habitat preference, regardless of phylogenetic propinquity (e.g. Arnold 1992;Losos 2011;Smith et al 2011;Kahrl et al 2018;Tarkhnishvili et al 2020;Cordero et al 2021;Grismer 2021;Kaatz et al 2021). Additionally, in many cases, unrelated species living in similar habitats may converge on the same morphology.…”
Section: Introductionmentioning
confidence: 99%
“…We followed a standardized statistical protocol for morphological analyses (Chan and Grismer 2021a) and employed multivariate analyses and data visualization methods recently used for other species of Xantusia (Grismer 2021) and commonly used in lizard taxonomy. Given that the three island populations are allopatric and there is no evidence of gene flow among them (Bezy et al 1980;Noonan et al 2013;Rice 2017), they were treated as independent evolutionary units regardless of their taxonomy (Smith 1946) so as to avoid violating the assumptions of statistical independence.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Whereas the continental species of Xantusia are relatively small (adult SVLs < 70 mm) microhabitat specialists (e.g. Zweifel and Lowe 1966;Bezy 1967;1989;Webb 1970;Lee 1975;Grismer and Galvan 1986;Levitt et al 2007;Noon et al 2013;Grismer 2021), the insular X. riversiana is much larger (adult SVLs 70-117 mm) and more of a habitat generalist but with possible inter-island differences in microhabitat preference, diet, and other aspects of their ecology (Fellers et al 1998(Fellers et al , 2008Fellers and Drost 1991;Mautz et al 1993;Drost et al 2018). Many studies across multiple lineages of lizards have demonstrated that morphology reflects habitat use as well as a number of other ecological traits (e.g.…”
Section: Introductionmentioning
confidence: 99%